2015
DOI: 10.1016/j.aoas.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Survey of insects & mite associated Cape gooseberry plants (Physalis peruviana L.) and impact of some selected safe materials against the main pests

Abstract: All experiments were conducted at the Experimental Farm of Plant Protection Research Station at Qaha, Qalubia Governorate, Egypt, throughout two successive growing seasons (2012 and 2013) on vegetative period. The results clearly indicated the presence of 36 species belonging to 25 families under 10 orders. These insects and mites are as follows:Insect species were clover leaf weevil, Phytonomus brunneipennis Boh.; clover root weevil, Sitona Lividipes Fahraeus; cutworm, Agrotis ipsilon (Huf.); green bug, Nezar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 6 publications
2
13
0
1
Order By: Relevance
“…A Physalis peruviana L., pertencente à família das Solanaceae, é uma fruta produzida em regiões tropicais (Afsah, 2015) e cultivada nas mais variadas épocas e manejos (Muniz et al, 2010), sendo destinada basicamente a dois segmentos: frutos para o processamento ou consumo in natura (Rufato et al, 2013).…”
Section: Introductionunclassified
“…A Physalis peruviana L., pertencente à família das Solanaceae, é uma fruta produzida em regiões tropicais (Afsah, 2015) e cultivada nas mais variadas épocas e manejos (Muniz et al, 2010), sendo destinada basicamente a dois segmentos: frutos para o processamento ou consumo in natura (Rufato et al, 2013).…”
Section: Introductionunclassified
“…Previous records. Africa: Algeria (Athias-Henriot 1957a), Egypt (Afsah 2015), Kenya (Migeon et al 2019), Lybia (Damiano 1961), Mauritius (Kreiter et al 2018), Morocco (McMurtry & Bounfour 1989, South Africa (Meyer 1981), Tunisia (Rambier 1972). Asia: China (Wu et al 1997), Cyprus (Vassiliou et al 2012), Iran (Hajizadeh & Mortazavi 2015), Israel (Swirski & Amitai 1968), Japan (Ohno et al 2012), Jordan (Allawi 1991), Philippine (Corpuz-Raros 2005, Syria (Barbar 2013), Turkey (Sekeroglu & Kazak 1993).…”
Section: Materials Examinedmentioning
confidence: 99%
“…Charles et al, (2006) indicated that the use of essential oil of alfazema is more effective in controlling the fennel aphid Hyadaphis foeniculi than essential oil of citronella. Bana, (2007) and Afsah (2015), indicated that solfan, KZ oil, and Achook had a great effect on the population density of some piercing-sucking pests attacking gooseberry. Lekha, (2002) and Chaudhary et al, (2015), studied the comparative efficacy of different neem-based biopesticides against aphids in coriander.…”
Section: Efficacy Of Different Treatments Against Aphid Species Of Fementioning
confidence: 99%
“…To protect crops from attacking these aphides, there are some conducted researching efforts to use some safe compounds for suppressing the effects of some piercing-sucking pests attacking the crops (Afsah, 2015 andMona andHomam, 2012).…”
Section: Introductionmentioning
confidence: 99%